Foreign Investment Decisions in Southern Bali’s Property Market: The Role of Economic Conditions, Investment Regulations, Behavioral, and Property Location - Louis, Karina; Setyari, Ni Putu Wiwin (International Journal of Social Science and Business, 2025)
This research examines factors influencing foreigners' investment decisions in Bali’s property market, focusing on economic conditions, foreign investment regulations, behavioral trends, and strategic location. A quantitative approach was applied, collecting data from 93 foreign property owners in Southern Bali (Badung Regency, Denpasar City, and Gianyar Regency) through structured questionnaires using a four-point Likert scale. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was utilized for data analysis, revealing that economic factors, behavioral trends, and property location significantly influence investment decisions, with property location being the strongest determinant. Conversely, foreign investment regulations had a positive but non-significant effect, suggesting that complex regulations do not strongly deter investors. These findings highlight the paradox of foreign investment in areas with restrictive ownership laws, emphasizing the necessity for enhanced investment policies, infrastructure development, and strategic urban planning. This research contributes to the discourse on international property investment, offering insights for policymakers, real estate developers, and financial advisors in creating a more conducive investment climate while balancing regulatory frameworks.